(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
While studying of the fauna of small mammals (Chiroptera, Insectivora, Rodentia) of Syunik region, new data on specific composition, distribution and abundance of species were obtained. The presence of a new area for specified species was identified. The obtained results were confirmed by conducted craniological and genetic analysis.